2001
DOI: 10.1016/s0735-1097(00)01037-8
|View full text |Cite
|
Sign up to set email alerts
|

Late rejection is a predictor of transplant coronary artery disease in children

Abstract: Late rejection is an independent predictor of TxCAD. Patients suffering severe late rejection develop angiographically apparent TxCAD rapidly and must be monitored aggressively. Both TxCAD mortality and morbidity occur early; therefore, we recommend immediate listing for re-Tx upon diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 10 publications
0
28
1
Order By: Relevance
“…We also chose not to categorize the degree of CAV as previous multicenter studies have done given the already small sample of patients in the groups [16,17]. Because our inclusion criteria required the diagnosis of CAV to be made by angiography or pathology, we may not have included patients who have microvascular disease that is difficult to detect by angiography, a known limitation of this gold standard diagnostic tool [18][19][20]. Despite these limitations, we were able to demonstrate that a significant number of children with CAV die suddenly.…”
Section: Discussionmentioning
confidence: 99%
“…We also chose not to categorize the degree of CAV as previous multicenter studies have done given the already small sample of patients in the groups [16,17]. Because our inclusion criteria required the diagnosis of CAV to be made by angiography or pathology, we may not have included patients who have microvascular disease that is difficult to detect by angiography, a known limitation of this gold standard diagnostic tool [18][19][20]. Despite these limitations, we were able to demonstrate that a significant number of children with CAV die suddenly.…”
Section: Discussionmentioning
confidence: 99%
“…Registry data demonstrates that CAV significantly contributes to late morbidity and mortality. Due to the lack of significant treatment options (Boucek et al, 2007;Schowengerdt, 2006;Musci et al, 1998;Razzouk et al, 1998;Mulla et al, 2001) 15% of recipients undergo cardiac re-transplant (Ross et al, 2006). Survival after re-transplant, however, is poorer than after a first heart transplant .…”
Section: Physiological Outcomesmentioning
confidence: 99%
“…The risk of an adverse outcome associated with an episode of rejection is related to the timing and severity of the event. The development of late rejection has been linked to transplant coronary artery disease (TCAD) and poor outcome [11, 14, 16]. In the pediatric population, studies have demonstrated that heart transplant recipients with a history of previous rejection episodes are at higher risk for symptomatic or fatal rejection [5].…”
Section: Introductionmentioning
confidence: 99%